2003
DOI: 10.1103/physrevlett.91.118701
|View full text |Cite
|
Sign up to set email alerts
|

Public Channel Cryptography by Synchronization of Neural Networks and Chaotic Maps

Abstract: Two different kinds of synchronization have been applied to cryptography: Synchronization of chaotic maps by one common external signal and synchronization of neural networks by mutual learning. By combining these two mechanisms, where the external signal to the chaotic maps is synchronized by the nets, we construct a hybrid network which allows a secure generation of secret encryption keys over a public channel. The security with respect to attacks, recently proposed by Shamir et al, is increased by chaotic s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(26 citation statements)
references
References 10 publications
(19 reference statements)
1
24
0
Order By: Relevance
“…Next to algorithmic extensions to further increase the security [21,22,15,23], architectural improvements or variants include a fully serial realisation with TDMA usage of a single TPM unit. This further decreases the area consumption but at the cost of an increase in necessary cycles for one output bit.…”
Section: Discussionmentioning
confidence: 99%
“…Next to algorithmic extensions to further increase the security [21,22,15,23], architectural improvements or variants include a fully serial realisation with TDMA usage of a single TPM unit. This further decreases the area consumption but at the cost of an increase in necessary cycles for one output bit.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first proposal [1] of the neural key-exchange protocol, improved strategies for the attackers [11,12] and the partners [5,13,14] have been suggested and analyzed [2,15,16,17]. For the geometric attack it has been found that the synaptic depth L determines the security of the system: the success probability P E decreases exponentially with L, while the synchronization time t sync increases only proportionally to L 2 [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…However, Kinzel [9,10,11] does not deal with the teacher-student relation since a teacher is not employed in his model. In contrast to Kinzel's model, we have proposed mutual learning between two students who learn from a teacher in advance [12].…”
Section: Introductionmentioning
confidence: 99%
“…As a model involving the interaction between students, Kinzel proposed mutual learning within the framework of on-line learning [9,10,11]. Kinzel's model employs two students, and a student learns with the other student acting as a teacher.…”
Section: Introductionmentioning
confidence: 99%